2014
DOI: 10.1080/10410236.2013.842526
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Direct and Indirect Effects of Exposure and Attention to Health Media on Intentions to Avoid Unprotected Sun Exposure

Abstract: Skin cancer is the most commonly diagnosed cancer in the United States, accounting for more than 2 million diagnoses and more than 9,000 deaths annually. A regional online survey of students enrolled at institutions of higher education (N = 1,251) examined (a) associations between health media use and intentions to avoid unprotected sun exposure and (b) theoretically derived health behavior constructs that may mediate the relationship between media use and individuals' decisions to avoid unprotected sun exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…In a similar study [25], Lovejoy, Riffe, and Lovejoy (2015) examined the relationship between health media usage and intentions to avoid unprotected sun exposure. Participants reported greatest health media exposure and attention to the Internet (mean exposure = 2.7 days, mean attention = 3.0 days), television (me = 1.6, ma = 2.5), magazines (me = 1.2, ma = 2.1), and newspapers (me = 1.1, ma = 2.0).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar study [25], Lovejoy, Riffe, and Lovejoy (2015) examined the relationship between health media usage and intentions to avoid unprotected sun exposure. Participants reported greatest health media exposure and attention to the Internet (mean exposure = 2.7 days, mean attention = 3.0 days), television (me = 1.6, ma = 2.5), magazines (me = 1.2, ma = 2.1), and newspapers (me = 1.1, ma = 2.0).…”
Section: Resultsmentioning
confidence: 99%
“…Participants reported greatest health media exposure and attention to the Internet (mean exposure = 2.7 days, mean attention = 3.0 days), television (me = 1.6, ma = 2.5), magazines (me = 1.2, ma = 2.1), and newspapers (me = 1.1, ma = 2.0). However, internet use was unrelated to unprotected sun exposure behavioral intentions [25]. It was reported that magazine usage was associated with more negative social attitudes regarding sun protective behavior, and less perceived control to decrease unprotected sun exposure ( p < 0.05, p < 0.001) [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the promotion of the tanned look as ideal decreased after 2006, it still was common throughout the study timeframe. This may partly explain why researchers have found magazine use to be associated with reduced behavioral control to avoid unprotected UV exposure [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results of an intervention to increase sun protection among adolescents illustrated treatment-to-mediator and mediator-to-behavior effects for the pros of sun protection and the pros of sun exposure as mediators (Adams, Norman, Hovell, Sallis, & Patrick, 2009). Attitudes toward sun protection and behavioral control to avoid unprotected sun exposure mediated the relationship between exposure to health information in television and sun protection behavioral intentions among college students (Lovejoy, Riffe, & Lovejoy, 2015). Jackson and Aiken (2000) reported that intention to sun protection and intention to sunbathe mediated the association between perception (perceived skin cancer risk and perceived benefits of tanning) and sun protection and sunbathing behavior among women.…”
mentioning
confidence: 99%